Proposed Business Strategy for "Routes" in Order to Penetrate Existing Marketing - Yulfa, Fadhil; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2015)
Abstract.Routes are a start up company that was founded by 5 sport enthusiast. They see an opportunity on the current market where number of people embracing sports as a lifestyle choice were in increasing. However, as a new player they facing a difficulties to penetrate the current market since all well known brand has high market share and has strong position in the market. To address these issue and formulate the suitable strategy for the future growth of Routes Company, author use qualitative data through observation, interview and literature study. By implementing external and internal analysis they encapsulate SWOT for Routes Company. Factors in the SWOT are used in the calculation of EFAS and IFAS then applied to the IE matrix and it shows that Routes positioned in cell number five called Hold and Maintain. In Hold and Maintain strategy, they have two alternative strategy than later author used QSPM matrix to show prefered strategy which end with market penetration. Author also using Porterâ€™s Generic Strategy to determine business level strategy and TOWS matrix for functional strategy. Business Model Canvas are used to elaborate the solution. In implementing the strategy, the author formulated some short term and long term action plan on for market penetration.Keyword: business strategy, sport apparel, business model canvasÂ Â